2022
DOI: 10.1002/lpor.202100636
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Magnetometer with Dual‐Coupling Optomechanics

Abstract: An experimentally feasible magnetometer based on a dual‐coupling optomechanical system is proposed, where the radiation‐pressure coupling transduces the magnetic signal to the optical phase, and the quadratic optomechanical interaction induces a periodic squeezing effect. The latter not only amplifies the signal to be measured, but also accelerates the signal transducing rate characterized by an experimentally observable phase accumulation efficiency. In the vicinity of opto‐mechanical decoupled time, the ulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Quantum information technologies have been exploited in different areas, such as quantum entanglement [1,2], quantum information storage [3,4], quantum logic gate [5,6], and so on. One of the significant applications is concerned with ultrasensitive detection, like mass sensors [7][8][9], charge sensors [10][11][12], quantum magnetometers [13][14][15] and force sensors [16][17][18]. For quantum precision measurement, enhancing weak signals and decreasing all kinds of noise can promote the signal-to-noise ratio (SNR).…”
Section: Introductionmentioning
confidence: 99%
“…Quantum information technologies have been exploited in different areas, such as quantum entanglement [1,2], quantum information storage [3,4], quantum logic gate [5,6], and so on. One of the significant applications is concerned with ultrasensitive detection, like mass sensors [7][8][9], charge sensors [10][11][12], quantum magnetometers [13][14][15] and force sensors [16][17][18]. For quantum precision measurement, enhancing weak signals and decreasing all kinds of noise can promote the signal-to-noise ratio (SNR).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, based on the linearized dynamics of the optomechanical interactions ω l ± 1Ω, a transparent window for the propagation of the probe field is induced by the incident field when the resonance condition is satisfied. It has been shown that this intriguing phenomenon provides a unique platform for achieving precision measurement [21][22][23][24][25][26][27][28][29], such as precision measurement of electrical charges with OMIT [23] and mass sensor with an optomechanical microresonator [24].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the generalized optomechanical system, which has a similar form of radiation-pressure-type interaction, and the interesting physical phenomenon of the sideband comb as well as the analogous laser action of magnons have been observed in the field of magnonics [38][39][40]. Moreover, a large number of studies have shown that nonlinear interaction between cavity fields and mechanical oscillation in the optomechanical system may provide metrology with a higher precision and require less power [28]; for example, the precision measurement of electrical charges beyond linearized dynamics [25,27], which can achieve the accuracy of measuring a single charge.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years optomechanical systems have been proven useful for sensing purposes due to the inherent nonlinear coupling between photons and mechanical modes. In particular, it has been shown theoretically that this nonlinearity can be used to achieve sensitivity in gravitational acceleration measurements many orders of magnitude higher than atomic interferometers [6,7,8,9], and can also be used effectively for magnetometry [10,11], precise force sensing [12,13,14,15], sideband cooling [16,17,18,19], and displacement sensing [20,14,21,22,23]. These works use different quantum resources to improve sensing, such as exploitation of quantum correlations, injection of squeezed states of light and implementation of nonlinear optomechanical resonators etc.…”
mentioning
confidence: 99%